The effect of polarity in the electrospinning process on PCL/chitosan nanofibres' structure, properties and efficiency of surface modification. (25th August 2017) - Urbanek, O.; Sajkiewicz, P.; Pierini, F.
Abstract: The aim of this research was to study the effect of charge polarity applied to the spinning nozzle on the structure and properties of polycaprolactone/chitosan (PCL/CHT) blends, in particular the efficiency of further surface modification by chondroitin sulphate (CS). The observed differences in the morphology and properties of fibres formed at different polarities were interpreted in terms of molecular interactions occurring in the system. FTIR results indicate stronger PCL-chitosan interactions at negative polarity, resulting in lower PCL crystallinity and crystal size distribution determined by DSC, as well as lower wettability. The charge polarity influences PCL/CHT fibre morphology and tailors some of their properties, e.g. wettability, mechanical properties and the efficiency of surface modification. Better efficiency of CS attachment was observed at negative polarity using atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS) is most probably related to higher chitosan content at the fibres' surface being attracted by the negative external potential. Graphical abstract: Highlights: The charge polarity influences the structure and properties of PCL/CHT. The negative charge polarity reduces the repulsion between chitosan molecules. The negative polarity increases molecular interactions between chitosan and PCL. The charge polarity influences efficiency of further surface medication process.